Foundations of Interprofessional Education in Dental Schools: A Narrative Review - Alqutaibi, Ahmed Yaseen; Rahhal, Mohamed M.; Awad, Rawda; Sultan, Omer Sheriff; Iesa, Mohamed A. M.; Zafar, Muhammad Sohail; Jaber, Mohamed (European Journal of Dentistry, 2025)
Interprofessional education (IPE) and interprofessional collaborative practice have gained significant recognition for their ability to enhance health care education and improve patient outcomes, particularly in dentistry. Given the close connection between oral and general health, incorporating IPE into dental curricula has become essential in preparing practitioners for collaborative patient-centered care. This review focuses on the foundations of IPE in dental schools, focusing on its role in preparing students for collaborative health care. It discusses the evolution and current trends of IPE, examples of existing programs, and the importance of interprofessional teamwork for dental students. Key interprofessional competencies, such as communication, ethics, and teamwork, are highlighted, along with methods for assessing these skills, emphasizing the value of IPE in developing well-rounded dental professionals.
Keywords: dental education; interprofessional collaboration; educational environment; IPE curriculum; learning theory